1. ## more derivatives

(1 pt) If , find .

=(3x^(3)-6)x^-4 = 3x^(-1)-6

f ' (x) = -3/x^2

If
find .

f ' (x) = (12x+2)/(2x^(3/2))

whats the error?

2. Originally Posted by wannous
(1 pt) If , find .

=(3x^(3)-6)x^-4 = 3x^(-1)-6

f ' (x) = -3/x^2

If

find .

f ' (x) = (12x+2)/(2x^(3/2))

whats the error?
we should see your work to determine if it correct or wrong.
Try to simplify the function first; to make the differentiation step easier.
1- $\displaystyle \frac{3x^3-6}{x^4}=\frac{3}{x}-\frac{6}{x^4}=3x^{-1}-6x^{-4}$.

2- $\displaystyle \frac{4x^2+2x+2}{\sqrt{x}}=4x^{\frac{3}{2}}+2\sqrt {x}+2x^{-\frac{1}{2}}$.

3. Originally Posted by wannous
(1 pt) If , find .

=(3x^(3)-6)x^-4 = 3x^(-1)-6

f ' (x) = -3/x^2

If

find .

f ' (x) = (12x+2)/(2x^(3/2))

whats the error?
$\displaystyle (3x^3-5)x^{-4}=3x^{-1}-6x^{-4}$

$\displaystyle (4x^2+2x+2)x^{-\frac{1}{2}}=4x^{\frac{3}{2}}+2x^{\frac{1}{2}}+2x^ {-\frac{1}{2}}$

Sorry, I didn't see your post, General.

4. thank a lot i got both of them now